Is it the way she moves? New evidence on the gender wage growth gap in the early careers of men and women in Italy - Emilia Del Bono; Daniela Vuri (Institute for the Study of Labor (IZA), 2006)
This paper explores newly available Italian data derived from a 1:90 sample of social security administrative records (INPS) to investigate gender differences in pay during the initial stages of a worker's career. We find that a significant and growing pay differential between men and women emerges during the first years of labour market experience, and that gender differences are highest when workers move across firms. In particular, we find that the most significant gender gap in log wage growth is associated with job moves which take place within a very short period of time, involve positive wage growth and result in the highest salary increases. Moreover, this gender mobility penalty occurs mainly when workers move to larger firms and we show that this is most likely explained by the fact that women value more than men some of the characteristics of these jobs or employers. Overall our results suggest that job and firm characteristics, rather than differences in worker characteristics or across-the-board discrimination, are the most important determinants of the gender wage growth differential in the Italian labour market.
urn:nbn:de:101:1-2008050270
Keywords: 330